The Influence of Perceived Enjoyment and Perceived Playfulness on Intention to Continue Using the Netflix Application: A Study on Generation Z in Kolaka Regency - Ismi Aulia; Muhamad stiadi; Agus Zul Bay (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the influence of perceived enjoyment and perceived playfulness on intention to continue using the Netflix application, focusing on Generation Z users in Kolaka Regency. The rapid development of digital technology has transformed entertainment consumption behavior from conventional media toward streaming-based services that are more flexible, personalized, and easily accessible. Netflix has become one of the widely used digital entertainment platforms because it offers diverse content, personalized recommendations, and viewing experiences that align with users’ preferences. In the context of Generation Z, enjoyable and engaging user experiences are particularly important because this group is characterized as digital natives, tends to prefer varied content, and is likely to switch to other platforms when the experience does not meet their expectations. This study employed a quantitative approach using a survey method. The sample consisted of 100 Netflix users residing in Kolaka Regency, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that perceived enjoyment has a positive and significant effect on intention to continue using. This finding suggests that the higher the comfort, satisfaction, and enjoyment perceived by users, the stronger their intention to continue using Netflix. Furthermore, perceived playfulness also has a positive and significant effect on intention to continue using. This means that an interesting, curiosity-arousing, and attention-focused experience can strengthen users’ continuance intention. This study confirms that the continued use of digital entertainment applications is influenced not only by functional aspects but also by emotional value and interactive experiences perceived by users.